Análise direta de vestígios de explosivos empregando espectroscopia vibracional: uma proposta de auxílio à perícia - Adão Edson de Barcelos Junior (2017)
The increase in the number of incidents involving ATM attacks in Brazil is of concern to the authorities, especially in the Minas Gerais state. The use of explosives by criminals has aroused the authorities interest in identifying the materials used in these incidents in order to control the commercialization of the raw materials. Therefore, the use of analytical techniques that produce reliable and fast results with minimal consumption of materials and that dont compromise the physical integrity of the samples is fundamental in the forensic work. Thus, we look for develop a method applying the FTIR-ATR and Raman spectroscopic techniques to identify residues of explosives in ATM post-blast scenes. In this work, explosives based on ANFO, nitro groups and black gunpowder were analyzed. Explosives, as well as post-blast residues, were obtained in partnership with the Anti-Bomb Squad form BOPE-MG. In the explosives based on ANFO, the deformation bands of the NO3- group were observed in the infrared and Raman spectra, as well as the NH4+ group in the infrared. In the post-blast spectrum of ANFO in the infrared it wasnt possible to identify bands of NH4+ group. For the emulsion, a similarity was observed between the spectra. However, the post-blast Raman spectrum didnt present satisfactory results. In the explosives based on nitro groups, bands of deformation were identified referring to the nitro groups and the carbonic structures in the infrared and Raman spectra. In the post-blast spectra in the infrared it was possible to differentiate the spectra of the pure explosives, except for HMX. In the Raman spectrum in the PETN post-blast, only the carbonic signals could be identified. On the other hand, in the case of C4 it was possible to identify traces of C4 as well as post-blast residues. In the explosives based on black powder, bands were observed referring to the groups NO3- and the carbonic structures of the coal. In the post-blast, the signals referring to the nitrate group werent observed, both in infrared and Raman. In all post-blast Raman spectra, fluorescence interference was observed. The data obtained in this research made it possible to identify and characterize explosive materials by forensic researches. The spectroscopic techniques presented satisfactory and complementary results for the pre-blast samples, despite their limitations. However, only in the infrared was possible to identify the post-blast residues. The method was applied in the analysis of traces of explosives in banknotes, being possible to identify and characterize residues of the explosive used in the incident.